Influence of clay content on microstructure and flexural strength of in situ reaction bonded porous SiC ceramics. (2020) - Das, Dulal; Kayal, Nijhuma
Abstract: The aim of the present study is to reveal the effects of clay contents on in situ reaction bonding of SiC, phase development, microstructure, porosity and mechanical properties of porous SiC ceramics. Porous silicon carbide (SiC) ceramics are prepared in air at 1400 °C for 1 h using alumina as bond phase additive and variable amount of clay as sintering aids and compared their properties. The ceramics prepared with only alumina additive obtained with flexural strength of 28 MPa at porosity 38 vol% without any characteristic peak for mullite. The mullitization was almost completed at 1400 °C with addition of 3 wt% clay. It was found that the addition of clay strongly promoted the phase transformation towards mullite at lower temperature. A high flexural strength of 72 MPa was achieved at porosity level of 33 vol% in the sample prepared with 5 wt% clay due to the enhancement of necks at the contacting points.